2016
DOI: 10.1080/13854046.2016.1257069
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury history is associated with earlier age of onset of Alzheimer disease

Abstract: Objective This study examined whether a history of traumatic brain injury (TBI) is associated with earlier onset of Alzheimer disease (AD), independent of apolipoprotein ε4 status (Apoe4) and gender. Method Participants with a clinical diagnosis of AD (n=7625) were obtained from the National Alzheimer’s Coordinating Center Uniform Data Set, and categorized based on self-reported lifetime TBI with loss of consciousness (LOC) (TBI+ vs TBI-) and presence of Apoe4. ANCOVAs, controlling for gender, race, and educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 54 publications
5
55
0
1
Order By: Relevance
“…These results confirm prior studies, including a 2008 Institute of Medicine report, 8 that have found an association between moderate to severe TBI and risk of dementia. 1,8,11,13,21,40 In addition, although prior studies of the association between mild TBI and dementia have been mixed, [2][3][4][5][6] our study adds to the weight of evidence suggesting that mild TBI is also associated with increased dementia diagnosis risk. [14][15][16]37,41 Our results differ from several recent cohort studies that found no association between self-reported mild TBI and dementia risk.…”
Section: Discussionmentioning
confidence: 81%
“…These results confirm prior studies, including a 2008 Institute of Medicine report, 8 that have found an association between moderate to severe TBI and risk of dementia. 1,8,11,13,21,40 In addition, although prior studies of the association between mild TBI and dementia have been mixed, [2][3][4][5][6] our study adds to the weight of evidence suggesting that mild TBI is also associated with increased dementia diagnosis risk. [14][15][16]37,41 Our results differ from several recent cohort studies that found no association between self-reported mild TBI and dementia risk.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study found that mild TBI is associated with a two‐fold increase in the risk of dementia diagnosis 173 . Another study found that people with a history of TBI who develop Alzheimer's do so at a younger age than those without a history of TBI 174 . Whether TBI causes Alzheimer's disease, other conditions that lead to dementia, or both, is still being investigated.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…Es gibt Hinweise, dass schwere SHT das Auftreten eines M.Alzheimer beschleunigen können (LoBue et al 2017). Eine Übersicht stellt die Assoziation mit M.Alzheimer in Frage, sondern sieht eher eine Assoziation mit anderen neurodegenerativen Erkrankungen (Weiner et al 2017).…”
Section: Vorgezogene Dementielle Entwicklungunclassified